Potential of Waste Biomass from the Sugar Industry as a Source of Furfural and Its Derivatives for Use as Fuel Additives in Poland - Magdalena Modelska; Michal J. Binczarski; Piotr Dziugan; Szymon Nowak; Zdzisława Romanowska-Duda; Adam Sadowski; Izabela A. Witońska (Energies, 2020)
Poland is one of the leading producers of sugar from sugar beet in Europe. However, the production of sugar generates large amounts of lignocellulosic waste, in the form of beet pulp and leaves. Currently, this waste is not reutilized in the chemical industry, but is only used as food for farm animals. This paper assesses the potential of using bio-waste from the sugar industry as a raw material for the production of furfurals via acid hydrolysis. Further processing of furfural into derivatives such as furfuryl alcohol (FA) or tetrahydrofurfuryl alcohol (THFA) could increase the economic profitability of the initiative. Furfuryl alcohol can be used as a fuel additive in sugar factories. Tetrahydrofurfuryl alcohol can be used as a component in agricultural fertilizers, increasing the yield of sugar beet. This approach reduces the amount of post-production waste and brings the sugar industry closer to the concept of a circular economy.